Positive electrode active material, preparation method thereof, positive electrode plate comprising positive electrode active material, secondary battery and electric device
Patent Information
- Application Number
- CN202380043121.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-01-17
AI Technical Summary
The existing cathode active materials of sodium-ion secondary batteries have a high water content, which affects the electrochemical performance, energy density and safety performance of the pole pieces and batteries, and the existing drying methods are difficult to meet the low water content requirements.
A composite of NaxRy(PO4)z(P2O7)k and C is used as the positive electrode active material. By controlling the ventilation volume and heating rate of the sintering atmosphere, a phosphate sodium salt positive electrode active material with a water content of no more than 1600 ppm is prepared. It is further crushed and baked. The dry step reduces the water content.
It significantly improves the processability of the cathode active material, increases the charge-discharge specific capacity and first-cycle Coulomb efficiency of the cathode plate, and ensures the cost effectiveness and performance optimization of the material.
Smart Images

Figure 00000027_0000 
Figure 00000027_0001 
Figure 00000027_0002
Abstract
Description
Positive electrode active material, preparation method thereof, positive electrode sheet containing same, secondary battery and electric device Technical Field
[0001] The present application relates to the technical field of sodium batteries, and in particular to a positive electrode active material, and a positive electrode sheet, a secondary battery, and an electrical device containing the positive electrode active material. Background Art
[0002] Secondary batteries are an ideal candidate for energy storage technology. While lithium-ion secondary batteries have achieved tremendous success in a variety of applications, the relative scarcity and high cost of lithium resources have drawn attention to sodium, a readily available and abundant material with similar performance to lithium. Sodium-ion secondary batteries are considered a promising candidate for future energy storage systems. However, the high water content in the sodium-ion cathode active materials used in existing technologies can affect the electrochemical performance, energy density, and safety of the electrode and battery.
[0003] In view of the above problems, it is necessary to provide a low-water content sodium phosphate positive electrode active material, which can effectively improve or even avoid the problem of positive electrode active material being associated with water content during slurry processing, so that the battery positive electrode sheet and secondary battery have higher charge and discharge specific capacity and first-cycle coulomb efficiency.
[0004] Summary of the Invention
[0005] In order to achieve the above-mentioned objectives, the present application provides a positive electrode active material, and a positive electrode sheet, a secondary battery and an electrical device containing the same.
[0006] The first aspect of the present application provides a positive electrode active material, wherein the positive electrode active material is Na x R y (PO4) z (P2O7) k and C, wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R comprises at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; wherein the water content of the positive electrode active material is not higher than 1600 ppm. The positive electrode active material of the embodiment of the present application has a low water content, which can effectively improve or avoid the problem of slurry instability (e.g., gelation) of the positive electrode active material, thereby significantly improving its processability and enabling the positive electrode sheet to have a higher charge and discharge capacity and a higher first-cycle coulombic efficiency.
[0007] In any embodiment, the water content is not higher than 1400 ppm, optionally not higher than 1200 ppm, optionally not higher than 1000 ppm, optionally not higher than 900 ppm, optionally not lower than 50 ppm, more optionally not lower than 70 ppm, and even more optionally 200-800 ppm. Positive electrode active materials having the above water content ranges are more cost-effective while ensuring that the materials have the above-mentioned advantageous properties.
[0008] In any embodiment, the chemical composition of the positive electrode active material satisfies at least one of the following conditions:
[0009] (1)3≤x≤5;
[0010] (2)2≤y≤4;
[0011] (3)1.5≤z≤2;
[0012] (4)1≤k≤1.5;
[0013] (5) R is Fe.
[0014] Such positive electrode active materials have a high energy density.
[0015] The second aspect of the present application provides a method for preparing a positive electrode active material, wherein the positive electrode active material is Na x R y (PO4) z (P2O7) k and C, wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R comprises at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; wherein the water content of the positive electrode active material is not higher than 1600 ppm; and the method comprises the following steps:
[0016] a) preparing a precursor material: preparing a mixed slurry comprising an R source compound, a sodium source compound, a phosphorus source compound, and a carbon source compound, and drying the mixed slurry to obtain the precursor material;
[0017] b) sintering the precursor material in a sintering atmosphere to obtain the positive electrode active material, wherein the ratio between the ventilation volume value of the sintering atmosphere and the weight value of the precursor material is 0.85-3.42m 3 / kg, optionally 1.70-3.42m 3 / kg, more preferably 2.27-3.42m 3 / kg.
[0018] The positive electrode active material prepared by the above method has low water content and good processability, and gives the positive electrode sheet and battery containing the material a higher charge and discharge specific capacity and a higher first-cycle coulombic efficiency.
[0019] In any embodiment, in step b), the heating rate is 0.5-5°C / min, optionally 2-5°C / min. Such a heating rate is helpful to obtain a positive electrode active material with a lower water content.
[0020] In any embodiment, in step b), the sintering atmosphere includes nitrogen and / or argon.
[0021] In any embodiment, in step b), the nitrogen flow rate is 2-10 L / min, optionally 5-10 L / min; and / or the sintering time is about 10-30 hours, optionally about 18-23 hours.
[0022] Adopting the above conditions in step b) can further help the prepared positive electrode active material to have a lower water content.
[0023] In any embodiment, the method of the present application further comprises the following steps:
[0024] c) pulverizing the positive electrode active material, wherein the pulverizing is performed at an ambient humidity of no more than 10%, and optionally at an ambient humidity of 2% to 10%. Controlling the ambient humidity during the pulverizing step facilitates ensuring that the pulverized positive electrode active material has a water content comparable to, or even lower than, that of the discharged material.
[0025] In any embodiment, the method of the present application further comprises the following steps:
[0026] d) drying the positive electrode active material. The drying step can further reduce the water content of the material.
[0027] The third aspect of the present application further provides a positive electrode plate, comprising the positive electrode active material of the first aspect or the positive electrode active material obtained by the method of the second aspect of the present application.
[0028] The fourth aspect of the present application further provides a secondary battery, comprising the positive electrode sheet of the third aspect of the present application.
[0029] The fifth aspect of the present application further provides an electrical device comprising the secondary battery of the fourth aspect of the present application.
[0030] The present application provides a low-water content sodium phosphate-based positive electrode active material, which can effectively improve the processability of the positive electrode active material (for example, slurry gel), thereby enabling the battery positive electrode plate to have a higher charge and discharge specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.
[0032] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .
[0033] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0034] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.
[0035] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.
[0036] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0037] Description of reference numerals:
[0038] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 housing; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0039] Below, with appropriate reference to the accompanying drawings, the embodiments of the positive electrode active material and its preparation method, the positive electrode sheet, the secondary battery and the electric device of the embodiment of the present application are described in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0040] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0043] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0044] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0045] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0046] Secondary batteries are an ideal choice for energy storage technology. Although lithium-ion secondary batteries have achieved great success in various applications, the relative scarcity and high cost of lithium resources have led people to turn their attention to sodium, which has similar properties to lithium but is abundant and readily available. Sodium-ion secondary batteries are also considered to be a strong candidate for future energy storage systems.
[0047] At present, a variety of positive electrode active materials for sodium ion batteries have been reported. Among them, sodium phosphate salts are considered to be the most promising positive electrode active materials for sodium ion secondary batteries because they combine multiple advantages including low cost, environmental friendliness, high theoretical capacity, high average operating voltage and low volume expansion. However, the water content of such materials in the prior art is relatively high. In the preparation of non-aqueous slurries, the material is more sensitive to the water content. Even a very small amount of water may cause the slurry to gel, making coating difficult, and further affecting the electrochemical performance and energy density of the electrode and battery. In addition, the increase in the water content of the positive electrode active material will make it easier for sodium in the bulk phase of the material to escape, resulting in residual alkali on the surface of the material, namely sodium bicarbonate, sodium hydroxide, sodium ions, etc., which reduces the kinetic performance of the electrode material during the charge and discharge process and causes battery flatulence during the cycle.
[0048] Although in order to improve the above problems, drying methods are generally used in the art to reduce the moisture content of the material, the ability of drying to reduce the moisture content is very limited and cannot meet the needs.
[0049] In view of the above problems, the present application provides a low-water content sodium phosphate salt positive electrode active material and a method for preparing a low-water content sodium phosphate salt positive electrode active material, which can effectively improve or even avoid the gel problem of the positive electrode active material during the processing process, thereby enabling the battery positive electrode sheet to have a higher charge and discharge specific capacity.
[0050] Positive electrode active material and preparation method thereof
[0051] One aspect of the present application is a positive electrode active material, wherein the positive electrode active material is Na x R y (PO4) z (P2O7) kand C, wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W and Pb; wherein the water content of the positive electrode active material is not higher than 1600 ppm.
[0052] Without wishing to be bound by any theory, the positive electrode active material of the embodiment of the present application has a low water content, which can effectively improve or avoid the problem of instability (e.g., gel) of the slurry of the positive electrode active material, thereby significantly improving its processability and enabling the positive electrode sheet to have a higher charge and discharge specific capacity and a higher first-cycle coulombic efficiency.
[0053] In this article, "gel problem" refers to the situation where the slurry is jelly-like and lacks fluidity, making it impossible to apply normally.
[0054] Although drying the positive electrode active material before slurry preparation can reduce its water content to a certain extent, it still cannot meet the low water content requirements of the material in the field. However, the positive electrode active material of the embodiment of the present application can have a lower water content, improving the processability of the slurry, thereby improving the performance of the electrode and battery, such as the charge-discharge specific capacity and the first-cycle coulombic efficiency.
[0055] As used herein, "water content" refers to the amount of water contained per unit mass of the positive electrode active material. The water content is measured in accordance with GB / T11133-2015 ("Petroleum products, lubricants and additives - Determination of water content by Karl Fischer coulometric titration").
[0056] Herein, the positive electrode active material means a material having the above-mentioned chemical composition, and it may be in different states, including, for example, a discharged state, a crushed state, and a dried state. Accordingly, the water content of the positive electrode active material includes the discharged water content, the water content after crushing, and the water content after drying. The discharged state is defined as the positive electrode active material after sintering (optionally preliminarily sieved), and the water content of the material at this time is the discharged water content. The crushed state is defined as the powder obtained by crushing the material in the above-mentioned discharged state, and the water content of the material at this time is the water content after crushing. The dried state is defined as the product obtained after drying the above-mentioned powder, and the water content of the material at this time is the water content after drying.
[0057] In some embodiments, the Na x R y (PO4) z (P2O7) k The complex with C is Na with carbon coating x R y (PO4) z (P2O7) k, wherein x, y, z, k and R are as defined above.
[0058] In some embodiments, the water content of the positive electrode active material is not higher than 1400ppm, optionally not higher than 1200ppm, optionally not higher than 1100ppm, optionally not higher than 1000ppm, optionally not higher than 950ppm, optionally not higher than 900ppm, optionally not higher than 850ppm, optionally not higher than 800ppm, optionally not higher than 750ppm, optionally not higher than 700ppm, optionally not higher than 650ppm. In some embodiments, the water content of the positive electrode active material is not lower than 50ppm, optionally not lower than 70ppm, optionally not lower than 200ppm, optionally not lower than 300ppm, optionally not lower than 350ppm, optionally not lower than 400ppm, optionally not lower than 450ppm, optionally not lower than 500ppm, optionally not lower than 550ppm. In some embodiments, the water content of the positive electrode active material is 200-800ppm. Although it is desirable for the positive electrode active material to have a lower water content, the positive electrode active material having the above water content range is more cost-effective while ensuring that the material has favorable properties.
[0059] In some embodiments, the chemical composition of the positive electrode active material satisfies at least one of the following conditions:
[0060] (1) 3≤x≤5, optionally 4;
[0061] (2) 2≤y≤4, optionally 3;
[0062] (3) 1.5≤z≤2, optionally 2;
[0063] (4) 1≤k≤1.5, optionally 1;
[0064] (5) R is Fe.
[0065] Such positive electrode active materials have a high energy density.
[0066] Another aspect of the present application provides a method for preparing the positive electrode active material described above, the method comprising the following steps:
[0067] a) preparing a precursor material: preparing a mixed slurry comprising an R source compound, a sodium source compound, a phosphorus source compound, and a carbon source compound, and drying the mixed slurry to obtain the precursor material;
[0068] b) Sintering: Sintering the precursor material in a sintering atmosphere to obtain the positive electrode active material, wherein the ratio between the ventilation value of the sintering atmosphere and the weight value of the precursor material is 0.85-3.42m 3 / kg, optionally 1.70-3.42m 3 / kg, more preferably 2.27-3.42m 3 / kg.
[0069] The positive electrode active material prepared by the above method has a low water content, good processability, and gives the positive electrode sheet and battery containing the material a higher charge and discharge specific capacity and a higher first-cycle coulomb efficiency. Without wishing to be bound by any theory, the method of the embodiment of the present application effectively reduces the water content (especially the discharge water content) of the positive electrode active material by controlling the sintering step. Low discharge water content is beneficial for the positive electrode active material to maintain or even further reduce the water content in possible further processing (such as crushing and / or drying, etc.). In particular, the ratio between the ventilation value of the sintering atmosphere in cubic meters in the sintering step and the weight value of the precursor material in kilograms is controlled within the above range to achieve a low water content of the positive electrode active material.
[0070] The discharge water content of the positive electrode active material obtained by the above steps is not higher than 1400ppm, optionally not higher than 1200ppm, optionally not higher than 1100ppm, optionally not higher than 1000ppm, optionally not higher than 950ppm, optionally not higher than 900ppm, optionally not higher than 850ppm, optionally not higher than 800ppm, optionally not higher than 750ppm, optionally not higher than 700ppm, optionally not higher than 650ppm. In some embodiments, optionally, the water content of the positive electrode active material is not lower than 50ppm, optionally not lower than 70ppm, optionally not lower than 200ppm, optionally not lower than 300ppm, optionally not lower than 350ppm, optionally not lower than 400ppm, optionally not lower than 450ppm, optionally not lower than 500ppm, optionally not lower than 550ppm. In some embodiments, the water content of the positive electrode active material is 200-800ppm.
[0071] Herein, “ventilation volume” means the total volume of sintering atmosphere gas introduced into the sintering equipment during the sintering time; that is, the ventilation volume (unit: m 3 )=sintering atmosphere gas flow rate*sintering time. For example, when the sintering atmosphere is nitrogen, the nitrogen amount (unit: m 3 ) = nitrogen flow rate (unit: L / min) * sintering time (unit: h) * 0.06. When the nitrogen amount is equal, the longer the sintering time, the smaller the corresponding nitrogen flow rate; the shorter the sintering time, the larger the corresponding nitrogen flow rate.
[0072] Herein, "sintering time" means the sum of the heating time, the holding time and the cooling time in the sintering step.
[0073] In some embodiments, in step a), the mixed slurry can be prepared, for example, by adding an R source compound, a sodium source compound, and a phosphorus source compound to a solvent to prepare a slurry; and then adding a carbon source compound to the slurry to obtain the mixed slurry.
[0074] In some embodiments, in step a), the solvent may be, for example, water (optionally, deionized water) or ethanol.
[0075] In some embodiments, in step a), the slurry and the mixed slurry can be prepared by one or more methods including grinding and solvent dispersion.
[0076] In some embodiments, in step a), the grinding can be performed in a manner conventional in the art, for example, the grinding can be ball milling, sand milling, vibration milling, or tumbling milling. The grinding can be performed using conventional equipment in the art (e.g., a ball mill, sand mill, vibration mill, or tumbling mill).
[0077] In some embodiments, the R source compound can be any compound in the art that can provide the R element. When the R element is Fe, the R source compound can be, for example, at least one of ferrous oxalate, ferric nitrate, ferric citrate, and ammonium ferric citrate.
[0078] In some embodiments, the sodium source compound can be any compound known in the art that can provide sodium. Such a compound can be, for example, at least one of sodium pyrophosphate, sodium acetate, sodium nitrate, sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.
[0079] In some embodiments, the phosphorus source compound can be any compound known in the art that can provide phosphorus. Such a compound can be, for example, at least one of ammonium dihydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium pyrophosphate, and sodium dihydrogen phosphate.
[0080] In some embodiments, the carbon source compound is any compound known in the art that can provide carbon. Such a compound can be, for example, at least one of oxalic acid, ascorbic acid, formaldehyde, acetaldehyde, n-butyraldehyde, lactic acid, citric acid, malic acid, oxalic acid, adipic acid, citric acid, soluble starch, ascorbic acid, sucrose, and glucose. The carbon source compound helps improve the electrical conductivity of the material.
[0081] In some embodiments, in step a), the average particle size D of the solid matter contained in the mixed slurry obtained after grinding isv 50 can be 0.1-0.8 microns. Such a particle size range is conducive to further reaction of the material during the sintering process.
[0082] Herein, the average particle size D v "50" means the particle size corresponding to 50% of the particles in the volume distribution. The average particle size can be measured by conventional methods in the art, for example, using a laser particle size analyzer.
[0083] In some embodiments, in step a), the drying is performed by at least one of the following methods: forced air drying, vacuum drying, freeze drying, and spray drying.
[0084] In some embodiments, in step b), the sintering atmosphere includes nitrogen and / or argon; optionally, the sintering atmosphere also includes hydrogen. In some embodiments, the sintering atmosphere is nitrogen. Generally, sintering atmospheres are classified as inert atmospheres or reducing atmospheres. Herein, a sintering atmosphere of nitrogen and / or argon is considered an inert sintering atmosphere; a sintering atmosphere of nitrogen-hydrogen mixed gas or argon-hydrogen mixed gas is considered a reducing atmosphere. In some embodiments, in step b), the sintering atmosphere is nitrogen.
[0085] In some embodiments, in step b), the sintering atmosphere has an oxygen content of less than 100 ppm, optionally between 30 and 50 ppm. Controlling the oxygen content within this range helps reduce side reactions and improve material conductivity. The sintering atmosphere is introduced after the system (e.g., the sintering furnace) has been evacuated; the oxygen content is the amount of oxygen remaining in the system after evacuation.
[0086] In some embodiments, in step b), the nitrogen flow rate is 2-10 L / min, optionally 5-10 L / min.
[0087] In some embodiments, in step b), the sintering time is about 10-30 hours, optionally about 18-23 hours.
[0088] Without wishing to be bound by any theory, using the sintering time and / or nitrogen flow rate within the above respective ranges can further facilitate the prepared positive electrode active material to have a lower water content (especially the water content of the discharge material).
[0089] In some embodiments, in step b), the heating rate is 0.5-5°C / min. Alternatively, in some embodiments, the heating rate is 2-5°C / min. Without wishing to be bound by any theory, such a heating rate ensures a sufficient reaction while facilitating the timely discharge of water generated by the reaction, thereby contributing to the production of a positive electrode active material with a low water content (particularly the water content of the discharge material).
[0090] In some embodiments, in step b), the sintering is performed by at least one selected from the group consisting of a tube furnace, a vacuum box furnace, an explosion-proof box furnace, a pusher kiln, a roller kiln, a bell kiln, and a rotary kiln.
[0091] In some embodiments, the sintering of step b) includes a low-temperature sintering stage and a high-temperature sintering stage. The low-temperature sintering can be kept at a temperature of 300-350°C for 3-5 hours. The high-temperature sintering can be kept at a temperature of 500-550°C for 7-11 hours, optionally for about 10 hours. At this time, the holding time as described above means the sum of the low-temperature sintering holding time and the high-temperature sintering holding time. The heating time as described above means the sum of the time required for the temperature to rise from the initial temperature (for example, ambient temperature or room temperature (25°C)) to the low-temperature sintering temperature and the time required for the low-temperature sintering temperature to rise to the high-temperature sintering temperature.
[0092] In some embodiments, the method further comprises the following steps:
[0093] c) pulverizing the positive electrode active material, wherein the pulverizing is performed at an ambient humidity of no greater than 10%, and optionally at an ambient humidity of 2% to 10%. Without wishing to be bound by any theory, controlling the ambient humidity during the pulverizing step is advantageous in ensuring that the pulverized positive electrode active material has a water content comparable to, or even lower than, that of the discharged material.
[0094] The water content of the positive electrode active material after crushing is not higher than 1500ppm, optionally not higher than 1200ppm, optionally not higher than 1100ppm, optionally not higher than 1000ppm, optionally not higher than 950ppm, optionally not higher than 900ppm, optionally not higher than 850ppm, optionally not higher than 800ppm, optionally not higher than 750ppm, optionally not higher than 700ppm, optionally not higher than 650ppm. In some embodiments, the water content of the positive electrode active material after crushing is not less than 50ppm, optionally not less than 70ppm, optionally not less than 200ppm, optionally not less than 300ppm, optionally not less than 350ppm, optionally not less than 400ppm, optionally not less than 450ppm. In some embodiments, the water content of the positive electrode material after crushing is 200-800ppm.
[0095] In some embodiments, the method further comprises the following steps:
[0096] d) drying the positive electrode active material.
[0097] The drying step in the present application can be carried out by conventional drying methods in the art, for example, vacuum drying, with a drying temperature of 100° C. to 200° C., optionally 110° C. to 150° C., and a drying time of 12 hours to 36 hours.
[0098] The water content of the positive electrode active material after drying is not higher than 1200ppm, optionally not higher than 1150ppm, optionally not higher than 1000ppm, optionally not higher than 900ppm, optionally not higher than 850ppm, optionally not higher than 800ppm, optionally not higher than 750ppm, optionally not higher than 700ppm. In some embodiments, the water content of the positive electrode active material after drying is not less than 50ppm, optionally not less than 70ppm, optionally not less than 200ppm, optionally not less than 250ppm. In some embodiments, the water content of the positive electrode active material after drying is 200-800ppm.
[0099] One aspect of the present application also provides a positive electrode active material prepared by the method described above.
[0100] Positive electrode sheet, secondary battery and electrical device
[0101] Another aspect of the present application provides a positive electrode sheet, which includes the positive electrode active material of the present application or the positive electrode active material obtained by the method of the present application.
[0102] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the embodiment of the present application.
[0103] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0104] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0105] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0106] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0107] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0108] Yet another aspect of the present application provides a secondary battery.
[0109] Herein, the secondary battery includes a battery cell form, a battery module form, and a battery pack form.
[0110] Another aspect of the present application provides an electrical device including the secondary battery according to the embodiment of the present application.
[0111] The battery cells, battery modules, battery packs, and electrical devices according to the embodiments of the present application are described below with reference to the accompanying drawings as appropriate.
[0112] Typically, a battery cell consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0113] [Negative electrode]
[0114] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0115] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0116] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0117] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0118] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0119] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0120] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0121] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0122] [Electrolytes]
[0123] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0124] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0125] In some embodiments, the electrolyte salt may be selected from sodium hexafluorophosphate (NaPF6), sodium hexafluoroborate (NaBF4), NaN(SO2F)2 (abbreviated as NaFSI), NaClO4, NaAsF6, NaB(C2O4)2 (abbreviated as NaBOB), NaBF2(C2O4) (abbreviated as NaDFOB), NaN(SO2R F )2 and NaN(SO2F)(SO2R F ) in one or more; wherein, R F Representative C b F 2b+1 , b is an integer in the range of 1-10, optionally an integer in the range of 1-3, more optionally, R F It is -CF3, -C2F5 or -CF2CF2CF3.
[0126] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0127] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0128] [Isolation film]
[0129] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0130] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0131] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0132] [Outer packaging]
[0133] In some embodiments, a battery cell may include an outer packaging for encapsulating the positive electrode sheet, negative electrode sheet, and electrolyte. For example, the positive electrode sheet, negative electrode sheet, and separator may be stacked or wound to form a laminated or wound cell structure, encapsulated within the outer packaging; the electrolyte is impregnated within the cell. The number of cells in a battery cell may be one or more, adjustable based on demand.
[0134] In one embodiment, the present application provides an electrode assembly. In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into the electrode assembly through a winding process or a lamination process. The outer packaging can be used to encapsulate the above-mentioned electrode assembly and electrolyte.
[0135] In some embodiments, the outer packaging of the battery cell may be a soft bag, such as a bag-type soft bag. The material of the soft bag may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. This application has no particular restrictions on the shape of the battery cell, which may be cylindrical, square, or any other arbitrary shape. For example, Figure 1 is a battery cell 5 of a square structure as an example.
[0136] In some embodiments, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0137] In some embodiments, battery cells may be assembled into a battery module or battery pack. The number of battery cells contained in a battery module or battery pack may be one or more, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery module or battery pack.
[0138] FIG3 shows an example battery module 4. Referring to FIG3 , in the battery module 4, multiple battery cells can be arranged sequentially along the length of the battery module 4. Of course, they can also be arranged in any other manner. Furthermore, the multiple battery cells 5 can be secured using fasteners.
[0139] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.
[0140] In some embodiments, the battery cells or the above-mentioned battery modules can be assembled into a battery pack. The number of battery cells or battery modules contained in the battery pack can be one or more. The specific number can be selected by those skilled in the art based on the application and capacity of the battery pack.
[0141] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0142] In addition, an embodiment of the present application further provides an electric device, which includes at least one of the battery cells, battery modules, or battery packs provided in the present application. The battery cells, battery modules, or battery packs can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0143] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0144] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0145] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0146] Example
[0147] Below, the embodiment of the present application is described. The embodiment described below is exemplary, is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiment, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0148] Example 1
[0149] 1. Preparation of the composite of Na4Fe3(PO4)2P2O7 and C as the positive electrode active material
[0150] a) Preparation of precursor materials:
[0151] According to the atomic molar ratio of Na, Fe, and P in the chemical formula Na4Fe3(PO4)2P2O7, 1.164 kg of sodium pyrophosphate decahydrate (Na4P2O7.10H2O), 1.367 kg of ferrous oxalate dihydrate (FeC2O4.2H2O), and 0.6 kg of ammonium dihydrogen phosphate (NH4H2PO4) were added to 6 L of water and ground and mixed; 0.117 kg of glucose was added thereto as a carbon source compound, and then stirred and sand-milled to obtain a mixed slurry, which was then spray-dried to obtain a precursor material;
[0152] b) Sintering:
[0153] 4 kg of precursor material was placed in a sintering furnace, and the sintering furnace was evacuated to control the oxygen content at 30-50 ppm. The sintering atmosphere was nitrogen with a nitrogen flow rate of 5.14 L / min. The precursor material was first heated from room temperature (25 ° C) to 300 ° C at a heating rate of 2 ° C / min, and maintained at 300 ° C for calcination for 4 hours. Then, the temperature was raised to 550 ° C at a heating rate of 2 ° C / min, maintained at 550 ° C for calcination for 10 hours, and then cooled to 100 ° C at a cooling rate of 2 ° C / min to obtain the product. X-ray diffraction (XRD) analysis and infrared carbon sulfur analyzer confirmed that the product was the desired positive electrode active material Na4Fe3 (PO4) 2P2O7 and C complex (carbon-coated Na4Fe3 (PO4) 2P2O7). The amount of nitrogen introduced during the sintering time was 6.825 m 3 The ratio of the weight of the precursor (in kg) was 1.70625. The material was transferred to a drying room for preliminary crushing and screening. At this time, the positive electrode active material was in the discharge state. The water content of the discharge was measured and recorded in Table 1.
[0154] c) Crushing:
[0155] The sintered positive electrode active material (i.e., the positive electrode active material in the discharged state) was subjected to air flow pulverization at an ambient humidity of less than 10% to obtain a positive electrode active material powder (in a pulverized state). The water content after pulverization was measured and recorded in Table 1.
[0156] d) Drying:
[0157] The positive electrode active material powder was placed in a drying oven at 120° C. and dried for 24 h to obtain the dried positive electrode active material powder (dried state). The water content of the positive electrode active material (i.e., the water content after drying) was measured and recorded in Table 1.
[0158] 2. Preparation of positive electrode sheet
[0159] The polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone, and then carbon black conductive agent and the dried positive electrode active material powder were added to make the weight ratio of positive electrode active material powder, carbon black conductive agent and binder 7:2:1 to prepare a uniformly dispersed positive electrode slurry. The positive electrode slurry was evenly coated on the surface of aluminum foil (aluminum foil thickness of 13μm, loading of 43.42mg / 1540.25mm 2 ), and then transferred to a vacuum drying oven for complete drying. The obtained electrode sheet is roll-pressed and then punched to obtain the positive electrode sheet.
[0160] 3. Preparation of negative electrode sheet
[0161] The carbon nanotube material, the binder sodium carboxymethyl cellulose and deionized water were stirred into a uniform slurry in a weight ratio of 4:1.6:94.4, and the slurry was coated on the surface of the copper foil (the copper foil thickness was 8 μm and the loading amount was 2 mg / 1540.25 mm 2 ), then transferred to a vacuum drying oven for complete drying, and then punched to obtain the negative electrode sheet.
[0162] 4. Preparation of Electrolyte
[0163] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether DME, and stirred evenly to obtain an electrolyte with a sodium salt concentration of 0.5 mol / L.
[0164] 5. Isolation film
[0165] Polypropylene film is used as the isolation film.
[0166] 6. Secondary Battery Preparation
[0167] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets to serve as an isolation. 0.5 g of the above electrolyte is added to assemble a laminated battery.
[0168] 7. Moisture content test
[0169] The test is carried out according to GB / T11133-2015 (Determination of water content in petroleum products, lubricants and additives - Karl Fischer coulometric titration).
[0170] 8. Charge and discharge specific capacity and first cycle coulombic efficiency test
[0171] The secondary battery prepared above was charged at 25°C at a constant current of 1 / 3C to 3.75V, and then charged at a constant voltage of 3.75V until the current dropped to 0.05C. The first cycle charge capacity (C c1 ); then discharge to 1.5V at a constant current of 1 / 3C, and measure the first cycle discharge capacity (C d1 ). Calculate the first cycle coulombic efficiency of the secondary battery according to the following formula:
[0172] Example 2-18
[0173] Except for the amount of nitrogen introduced (keeping the sintering time unchanged, changing the nitrogen amount by changing the nitrogen flow rate) and the sintering weight ratio or heating rate with the precursor (see Table 1 below for details), the other steps of Examples 2-18 are the same as those of Example 1.
[0174] Comparative Examples 1 and 2
[0175] Comparative Example 1 is substantially the same as Example 1, except that the ratio of the amount of nitrogen to the weight of the precursor is changed.
[0176] The sintering and drying conditions and test results in the above embodiments and comparative examples are shown in Table 1 below.
[0177] As can be seen from Table 1, in the examples, when the precursor weight and the heating rate are the same, the larger the ratio within the above range, the lower the water content (or the better the performance). Compared with Comparative Examples 1-2, the examples of the present application (the ratio between the ventilation volume value of the sintering atmosphere and the weight value of the precursor material is in the range of 0.85-3.42m 3 / kg range) to obtain a positive electrode active material with lower water content, and the water content of the positive electrode active materials in the examples of the present application is all lower than 1600ppm.
[0178] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, wherein the positive electrode active material is Na x R y (PO4) Z (P2O7) k and C, wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W and Pb; wherein the water content of the positive electrode active material is not higher than 1600ppm.
2. The positive electrode active material according to claim 1, wherein the water content is not higher than 1400 ppm, optionally not higher than 1200 ppm, optionally not higher than 1000 ppm, optionally not higher than 900 ppm, optionally not lower than 50 ppm, more optionally not lower than 70 ppm, and more optionally 200-800 ppm.
3. The positive electrode active material according to claim 1 or 2, wherein the chemical composition of the positive electrode active material satisfies at least one of the following conditions: (1)3≤x≤5; (2)2≤y≤4; (3)1.5≤z≤2; (4)1≤k≤1.5; (5) R is Fe.
4. A method for preparing a positive electrode active material, wherein the positive electrode active material is Na x R y (PO4) Z (P2O7) k and C, wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W and Pb; wherein the water content of the positive electrode active material is not higher than 1600ppm; the method comprises the following steps: a) preparing a precursor material: preparing a mixed slurry including an R source compound, a sodium source compound, a phosphorus source compound and a carbon source compound, and drying the mixed slurry to obtain the precursor material; b) sintering the precursor material in a sintering atmosphere to obtain the positive electrode active material, The ratio between the volume of the sintering atmosphere and the weight of the precursor material is 0.85-3.42 m 3 / kg, optional 1.70-3.42m 3 / kg, more preferably 2.27-3.42m 3 / kg.
5. The method according to any one of claims 4, wherein in the step b), the heating rate is 0.5-5°C / min, optionally 2-5°C / min.
6. The method according to claim 4 or 5, wherein in the step b), the sintering atmosphere comprises nitrogen and / or argon.
7. The method according to claim 6, wherein in the step b), the nitrogen flow rate is 2-10.5 L / min, optionally 5-10.5 L / min; and / or the sintering time is about 10-30 hours, optionally about 18-23 hours.
8. The method according to any one of claims 4 to 7, further comprising the following steps: c) pulverizing the positive electrode active material, wherein the pulverizing is performed at an ambient humidity of no more than 10%, optionally at an ambient humidity of 2% to 10%.
9. The method according to any one of claims 4 to 8, further comprising the following steps: d) drying the positive electrode active material. 10 . A positive electrode sheet, comprising the positive electrode active material according to claim 1 or the positive electrode active material obtained by the method according to claim 4 . A secondary battery comprising the positive electrode sheet according to claim 10.
12. An electrical device comprising the secondary battery according to claim 11.
Citation Information
Patent Citations
Core-shell structured sodium cobalt pyrophosphate / carbon positive electrode composite material, and preparation method and application thereof
CN107146883A
Positive electrode active material, aqueous solution sodium ion battery and electronic device
CN112510198A
Sodium ion battery and preparation method thereof
CN113611827A